THE STUDY OF WATER QUALITY STATUS IN THE NGEBRONG RIVER WITH PHYSICAL AND CHEMICAL PARAMETERS IN THE TAWANGSARI BARAT REGION, PUJON DISTRICT, MALANG REGENCY - Bambang Suharto; Liliya Dewi; Aulia Nur Mustaqiman; Tyas Roro Anggraini Kyai Marjo (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2019)
Aim: The purpose of this study was to determine the status of water quality in a river by using the Pollution Index method as stated in the Decree of the Minister of Environment No. 115/2003 regarding Guidelines for Determining the Status of Water Quality and to determine the effect of quality status on development efforts towards ecotourism. Methodology and Results: The measurement of water quality was carried out at two points, namely T1 (upstream) and T2 (downstream) points. The parameters included BOD, COD, DO, TSS, Temperature, pH, Zn, S, P, No3, and No2. From the test results for class I, II, and III criteria, almost all parameters exceeded the quality standard. The status of the river water quality, according to the Pollution Index, has increased from moderate polluted upstream and heavily polluted to certain parameters downstream. Conclusion, significance and impact study: The quality standards that are met for the river are criteria for class IV. The increase in pollution is indicated by human activity around the river which is characterized by increasing population and land use in agriculture and plantations. The increasing pollution reduces the quality of the river if it is developed into an ecotourism area due to its low water quality status.